Feasibility of Carbonaceous Nanomaterial-Assisted Photocatalysts Calcined at Different Temperatures for Indoor Air Applications - Wan-Kuen Jo; Kun-Hwan Kim (International Journal of Photoenergy)
This study examined the characteristics and photocatalytic activity of multiwall carbon nanotube-assisted TiO2 (MWNT-TiO2) nanocomposites calcined at different temperatures to assess their potential indoor air applications. It was confirmed that the composites calcined at low temperatures (300 and 400°C) contained TiO2 nanoparticles bound intimately to the MWNT networks. Meanwhile, almost no MWNTs were observed when the calcination temperature was increased to 500 and 600°C. The MWNT-TiO2 composites calcined at low temperatures showed higher photocatalytic decomposition efficiencies for aromatic hydrocarbons at indoor concentrations than those calcined at high temperatures. The mean efficiencies for benzene, toluene, ethyl benzene, and o-xylene (BTEX) by the composite calcined at 300°C were 32, 70, 79, and 79%, respectively, whereas they were 33, 71, 78, and 78% for the composite calcined at 400°C, respectively. In contrast, the efficiencies decreased to close to zero when the calcination temperature was increased to 600°C. Moreover, the MWNT-TiO2 exhibited superior photocatalytic performance for the decomposition efficiencies compared to TiO2 under conventional UV-lamp irradiations. Consequently, these carbonaceous nanomaterial-assisted photocatalysts can be applied effectively to indoor air applications depending upon the calcination temperature.